THE EFFECT OF DELAY IN TEMPERATURE VARIATIONS ON RESULTS OF GLUCOSE TEST IN DM PATIENTS WITH HYPERCHOLESTEROLEMIA - Khotul Ula, Chori; Edy Haryanto, Edy Haryanto; Syamsul Arifin, Syamsul Arifin; Istanto, Wisnu (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: The pre-analytic stage has the most significant contribution to error, which is 60% to 70%. This is an excellent contribution to the dependability of laboratory results. Delays in the examination often occur in the laboratory due to various factors influencing glucose examination outcomes. Purpose: To ascertain the effect of long delays in various temperatures on the results of plasma NaF and serum glucose tests in diabetes mellitus patients who have hypercholesterolemia. Method: Pre-test and post-test design used in a pre-experimental method. In the pretest, plasma NaF and serum glucose levels were checked immediately. In the posttest, the plasma NaF and serum samples were delayed for 4 and 8 hours at the temperature of the refrigerator (4°C) and room temperature (25°C). Result: The results of One-way ANOVA test analysis of the plasma NaF glucose level with an immediate examination, a delay of 4 and 8 hours at room temperature (25°C) showed no effect with a Sig. of 0.423 > 0.05. Plasma NaF glucose level with an immediate examination, 4 and 8 hours delay in refrigerator temperature (4°C) showed no effect with Sig. of 0.772 > 0.05. Serum glucose levels with an immediate examination, 4 and 8 hours delay at room temperature (25°C) showed no effect with a Sig. of 0.333 > 0.05. Serum glucose levels with an immediate examination, 4 and 8 hours delay in refrigerator temperature (4°C) showed no effect with a Sig. of 0.604 > 0.05. Conclusion: There was no effect of 4 hours and 8 hours of delay at the temperature of the refrigerator (4°C) and room temperature (25°C) on the results of NaF and serum glucose examinations in patients with diabetes mellitus who have hypercholesterolemia.